Digging deeper into the state-democracy nexus: The role of civic participation in fostering impartial bureaucracy - Andrea Vaccaro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The growing body of research on the relationship between the state and democracy has remained inconclusive both in terms of causal direction and sign. One key factor contributing to this inconclusiveness is the lack of precision in the conceptualization and measurement of democracy and state capacity. Drawing on this argument, my study takes an original approach to the topic by shifting the focus on more specific aspects of the two concepts. Through a statistical analysis of two precise attributes of democracy and state capacity-namely, civic participation and impartial bureaucracy-my study provides new evidence on their dynamic relationship in a comparative cross-country setting of over 160 countries after World War II. My findings strongly support the hypothesis that a vibrant civic society is an important prerequisite of impartial bureaucracies. They also highlight the importance of digging deeper into the concepts of democracy and state capacity to achieve a more thorough understanding on the state-democracy nexus and its underlying mechanisms.
Keywords: 330; democracy; state capacity; civic participation; impartial bureaucracy; state-democracy nexus